answersLogoWhite

0

3x**2+x-10

Multiply first and last terms

3*-10=-30

Find factors of -30 that add up to second term

6+-5=1

rewrite

3x**2-5x+6x-10

Factor pairs of terms

3x**2-5x+6x-10 = x(3x-5)+2(3x-5)

Factor

x(3x-5)+2(x-5) = (x+2)(3x-5)

User Avatar

Wiki User

14y ago

Still curious? Ask our experts.

Chat with our AI personalities

MaxineMaxine
I respect you enough to keep it real.
Chat with Maxine
LaoLao
The path is yours to walk; I am only here to hold up a mirror.
Chat with Lao
RafaRafa
There's no fun in playing it safe. Why not try something a little unhinged?
Chat with Rafa
More answers

X2 + 3x - 10

What two factors of - 10 add up to 3 ?

(x + 5)(x - 2)

===========

User Avatar

Wiki User

12y ago
User Avatar

Add your answer:

Earn +20 pts
Q: How would you factor 3x squared plus x minus 10?
Write your answer...
Submit
Still have questions?
magnify glass
imp